Studies on Vacuum Singulation of Seeds for Sowing Nursery Plug Trays - Gaikwad, Bhaskar; Sirohi, N.P.S; Kumar, Adarsh (Journal of Agricultural Engineering, 2007)
Precision seeding in nursery plug trays requires placement of single seed in each cell. In mechanical seeding, this requirement can be met by vacuum singulation of seeds and dropping one seed in individual cells. Studies were conducted to determine optimum combination of suction pressure and nozzle size for the singulated picking of tomato and capsicum seeds. Sixteen combinations of different nozzle sizes and suction pressures were evaluated for singulation and seeding of these seeds in plug trays. The suction pressure was found to influence picking of single seed the most followed by nozzle size for both, capsicum and tomato seeds. The optimum combination of suction pressure and nozzle hole size for more than 90% singles in the case of capsicum was 500 mm of water column (4.91 kPa) and 0.49 mm and for tomato it was 400 mm of water column (3.92 kPa) and 0.46 mm, respectively.